Enhancement of QoS in voice-enabled networks using combination of MPLS and DiffServ - Ahmed Alsoudi, Essam Mutahar (2014)
At its beginnings, the Internet Protocol was not meant for real-time applications such as voice and video. These conventional IP networks were limited to providing only best-effort QoS model which implies no QoS. Now voice traffic has been transmitted to IP-based networks instead of the conventional Public Switched Telephone Network (PSTN). Therefore, early adopters of this technology have noticed that for voice traffic to function as well as on conventional IP-based network as in PSTN, the transport techniques used by the IP-based network needed some additional policies and technique in place to accommodate the requirements of real-time data traffic. DiffServ is another QoS model used in IP networks, which differentiates IP traffic into classes each with certain priority. Implementing DiffServ, alone, can meet the SLA requirement in term of providing different QoS techniques based on the traffic type, but cannot ensure bandwidth, perapplication basis, so congested path may cause jitter, end to end delay or packet loss. MPLS was developed to combine the advantages of the connectionless layer 3 routing and the connection-oriented layer 2 forwarding, and provides per-hop data forwarding where it uses the label swapping rather than the layer 3 complex lookups in a routing table. Implementing MPLS, alone creates an end to end path with bandwidth reservations which guarantees the availability of resources to carry traffic of volume less than or equal to the reserved bandwidth, but MPLS is not aware of the DiffServ classes which considered as a disadvantage. This research project demonstrated the usefulness of combining DiffServ and MPLS in voice-enabled network to enhance voice quality by reducing end to end delay, jitter, and packet loss and proposed a method for analyzing voice applications’ requirements based in DiffServ-aware MPLS network.